Kinerja saham akselerasi dalam isu inflasi: Kasus sektor konsumen non-primer - Gianna Angela (Manajemen Bisnis dan Keuangan Korporat, 2023)
The consumer cyclical sector is a sector that has a close relationship with changes in economic conditions. In February 2023, inflation was at its highest point and was at its lowest point in May 2023. Based on this phenomenon, this study aims to determine the condition of stock returns in the issue of national inflation. This study finds that the optimal performance of stock returns of the consumer cyclical sector occurs in April 2023. This study finds that the highest volatility occurs in May 2023 while the lowest volatility occurs in April 2023. This condition implies that the difference in stock returns occurs between the points highest with a relatively low point of inflation.